Bimbingan Teknis Pembuatan Pakan Ternak Menggunakan Bahan Baku Lokal di Sulawesi Tenggara - Pagala, M.A.; Zulkarnain, D.; Badaruddin, R.; Hadini, H. (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2020)
The current fact shows that commercial animal feeds fulfill the local market in Southeast Sulawesi, which come from outer South East Sulawesi, in particular from South Sulawesi and Java. This commercial feed price certainly is not cheap and tend to rise every year that decrease the ability of cattleman as buyers. According to this, the existence of alternative feed with reachable price by a consumer (cattleman) is largely and potentially as a market segment. Through this PKM project of making a feed that meets technical qualification as qualified feed(good feed) and eatable feed(safe feed). The technology for the production process that has been chosen and applied in this organic feed making venture is using the approach ofâ€ green biotechnology, â€œ which is eco-friendly. This PKM local feed program using processing staple waste to feed with various processing technics such as chemical processing (hydrolysis), mechanic (steaming and siege), and biological (fermentation). The result has been reached from this activity is enhancing the knowledge and comprehension of cattleman groups. These useful for their enterprise sustainability expansion with the utilization of local feed ingredients as their cattle feed, so that can decrease expensive feed cost and increase cattleman welfare.